From Digital Consumption to Digital Invention: Toward a New Critical Theory and Practice of Multiliteracies. Issue 1 (2nd January 2018) - Mirra, Nicole; Morrell, Ernest; Filipiak, Danielle
Abstract : The teaching of media and digital literacies has gained increased attention in the 20 years following the New London Group's landmark publication. From approaches urging the study of popular culture to calls for youth led social media revolution, there is no shortage of approaches. Yet scant attention is offered toward articulating a new and comprehensive theory of pedagogy and production that acknowledges the changing tools and technologies at young people's disposal, conceptualizes young people as media producers, and applies these developments to today's complex classroom context. We aim to articulate a new critical theory of multiliteracies that encompasses 4 types of digital engagement: (a) critical digital consumption, (b) critical digital production, (c) critical distribution, and (d) critical digital invention. We make the argument that a new critical theory of multiliteracies needs to account for each of these types of digital engagement but that, ultimately, we must move beyond theorizing our youth as passive consumers or even critical users of digital technologies toward the project of facilitating youth communities of digital innovation.